Characterization of oocyte retrieval cycles with empty zona pellucida. (8th December 2017) - Oride, Aki; Kanasaki, Haruhiko; Hara, Tomomi; Ohta, Hiroko; Kyo, Satoru
Abstract: Purpose: To identify the factors that characterize cycles with empty zona pellucida (EZP). Methods: Thirty‐six oocyte retrieval cycles from which EZP were collected and another 36 cycles from which no EZP was collected were compared. The patients were divided into three groups: those with no EZP collected during any cycle, those with EZP collected during all cycles, and those experiencing cycles both with and without EZP. Results: The mean number of oocytes collected per cycle was higher in the cycles with EZP than without EZP. The fertilization rate of the collected oocytes and the rate of good embryo formation were significantly lower in the cycles with EZP. No significant difference was observed between the three groups in terms of age, number of oocytes collected, or hormone levels before and after the oocyte retrieval. The fertilization and pregnancy rates were highest in the patients with no EZP being collected during any cycle, followed by those experiencing cycles both with and without EZP, and then by those with EZP collected during all cycles. Conclusion: The observation of lower fertilization, poor embryo formation, and a low pregnancy rate in the patients with EZP suggests the poor quality of oocytes that were collected with EZP in the same cycle.